2015
DOI: 10.1002/jsfa.7391
|View full text |Cite
|
Sign up to set email alerts
|

Anti-adhesion activity of thyme (Thymus vulgarisL.) extract, thyme post-distillation waste, and olive (Olea europeaL.) leaf extract againstCampylobacter jejunion polystyrene and intestine epithelial cells

Abstract: Our findings suggest that TE, the agro-food waste material TE-R, and the by-product OE represent sources of bioactive phytochemicals that are effective at low concentrations and can be used as therapeutic agents to prevent bacterial adhesion. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 32 publications
8
34
0
Order By: Relevance
“…(van Alphen et al, 2012) had similar findings and observed that pre-exposure of C. jejuni to low concentrations of carvacrol modulated motility and invasion of INT-407 intestinal epithelial cells without affecting intracellular ATP levels or epithelial function. Reduced motility and attachment efficiency in C. jejuni on exposure to clove oil (Kovács, 2014), thyme (Pogacar et al, 2016), herbal extracts (Bensch et al, 2011), and campynexins (Johnson et al, 2015) have also been observed.…”
Section: Discussionmentioning
confidence: 98%
“…(van Alphen et al, 2012) had similar findings and observed that pre-exposure of C. jejuni to low concentrations of carvacrol modulated motility and invasion of INT-407 intestinal epithelial cells without affecting intracellular ATP levels or epithelial function. Reduced motility and attachment efficiency in C. jejuni on exposure to clove oil (Kovács, 2014), thyme (Pogacar et al, 2016), herbal extracts (Bensch et al, 2011), and campynexins (Johnson et al, 2015) have also been observed.…”
Section: Discussionmentioning
confidence: 98%
“…Antimicrobial activities are expressed as the MICs, in grams of FDSS per litre of medium, to assess the efficacies of the initial waste material (FDSS) for bioactive extract preparation. The antimicrobial efficacies of FDSS at concentrations equal to the MICs determined in the broth microdilution tests were also analysed using the macrodilution method, and thus determined as the percentage of bacterial growth inhibition after 4, 9 and 24 h …”
Section: Methodsmentioning
confidence: 99%
“…To promote the commercial value for these bioactive plant materials, it is important to define the potential use of these grape skin and seed phenolics, e.g. in terms of: (i) natural preservatives in the food and feed industry to avoid synthetic preservatives; (ii) alternative agents with potential for application to novel infection‐prevention strategies; (iii) nutrition or digestion aids, as they are absorbed and metabolized through normal pathways in humans to a large extent; and (iv) use in cosmetics, where plant extracts can cleanse the skin and promote quicker wound healing …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a successful reduction in biolm formation can be a potential strategy for the management of disease progression and elimination of a pathogen. 4,6 In this context, we have assessed the antibiolm property of PJE, 34 baicalein, 35 quercetin 36,37 and chrysin 38 against P. aeruginosa. Flavone compounds were reported to have antibacterial and antibiolm activity against bacteria.…”
Section: Discussionmentioning
confidence: 99%